Review of Image Representation in E-Commerce - Patel, Nayan; Mungase, Gaurav; Patil, Ram; Bodke, Amol (International Journal of Computer Sciences and Engineering, 2025)
In today’s E-Commerce market mostly all the vendors like Amazon, Flipkart, Snap deal and other E-Commerce websites are show its product in the form of 2D image. Our world is exist in 3D but we mostly use 2D view for see something virtually (include newspaper image, TV advertise, template). All these things are come under boundary and resist the customer to provide full view of product. So in this paper we are representing the positive points and drawbacks of the existing system. It will help to build the proposed system. Generally each e-commerce website show different views of products by uploading images in 2D view due to this customer face problem they can’t see the fully view of product. Very few websites shows their products in 3D view using flash player, but the problem with showing 3D view of product using flash player. First its static i.e. it will show the 3D view of the products with generated flash file. Second thing it needs flash player to run the 3D view of product. In this paper we represent existing system merits and demerits and give brief view about the present system.